NILAI-NILAI PENDIDIKAN PADA PROSES PEMBELAJARAN TARI DISEKOLAH DASAR - MUKHLISIN MUKHLISIN (STKIP Melawi, 2022)
Abstract: The learning process is not apart from the educational value that occursduring learning and teaching activities, including the Dance Learning Process inElementary Schools. This study examines the value of education in the dancelearning process in elementary schools. This study used qualitative methods, andan educational approach. Collecting data used observation techniques, interviews,and document studies. The data analysis procedure used data reduction, datapresentation and verification. Analysis of educational value in the dance learningprocess in elementary schools used Rosyadi and Hasbullah’s analysis. The validityof the data in this study used triangulation of data sources. The results are 1)Religious Value 2) Discipline Value; 3) Independent Value; 4) Social Value.Specifically, the findings of the dance learning process in elementary schools, thereis an educational value that is reflected by the dance learning process takes place.The benefits of research as a reference in learning the art of dance. Keyword: dance learning, educational value Abstrak: Proses pembelajaran tidak terlepas dari nilai pendidikan yang terjadiselama kegiatan belajar dan mengajar berlangsung, tak terkecuali dalam ProsesPembelajaran Tari di Sekolah Dasar. Penelitian ini mengkaji Nilai Pendidikan padaproses pembelajaran Tari di Sekolah Dasar. Penelitian ini menggunakan metodekualitatif, dan pendekatan pendidikan. Penggumpulan data menggunakan tekhnikobservasi, wawancara, dan studi dokumen. Prosedur analisis data menggunakanreduksi data, penyajian dan verifikasi data. Analisis nilai pendidikan pada prosespembelajaran Tari di Sekolah Dasar menggunakan Analisis Rosyadi danHasbullah. Validitas data dalam penelitian ini menggunakan trianggulasi sumberdata. Dengan hasil 1); Nilai Religius 2). Nilai Disiplin; 3). Nilai Mandiri; 4). NilaiSosial. Secara khusus temuan proses pembelajaran Tari di Sekolah Dasar, terdapatNilai Pendidikan yang tercermin saat proses pembelajaran Tari berlangsung.Manfaat penelitian sebagai rujukan dalam pembelajaran seni tari. Kata Kunci: pembelajaran tari, nilai pendidikan